Spaces for Native and Foreign-Born Parents: When Personal Thoughts Can Become an Opportunity for Learning - Raccagni, Dalila (INSTED: Interdisciplinary Studies in Education & Society, 2021)
Globalisation characterises our current century and, as a consequence of its worldwide spread, it affects a multiplicity of disciplines. In light of this phenomenon, the present article, which describes qualitative research in family pedagogy, focuses on foreign-born parents. The life stories of these parents provide an interesting point of reflection on the importance of recognising themselves as bearers of a unique history, despite being citizens of the world. The narrated and shared personal experience is characterised by relationships and thoughts that have helped form the individual. These same relationships re-present themselves in the present in the host country and challenge the subject to a daily learning experience. However, the learning and reflective moment is not limited to self-reflection. Therefore, it is fundamental for foreign-born parents to be able to interact with other subjects, who in turn are required to be welcoming towards the foreign parents. This is an attitude that requires fearlessness because a sense of security or fear towards others is an expression of the trust that a community has in itself. If one believes in the community’s ability to integrate other individuals within itself, then its members consequently have an attitude of openness towards the foreigner: in other words, they are not afraid of the different culture. This predisposition requires parents to adopt a logic of globalisation which includes rights and duties; it is a challenging task since the planetary dimension of citizenship cannot be achieved without a true commitment to reflection, active decision-making and education. Sustainable ecologies are associated with relationships, culture, ethnicity, and education. Therefore, it is important that within local communities spaces of encounter between parents are fostered, so that the thoughts of the individual can be shared. These spaces should be built with the awareness that human sustainability itself is often related to creating sufficient hope in individuals and communities, building meaningful dialogue and an experience of communion through all the differences. In these contexts, the subject as such lives a continuous educational and formative experience, which leads them towards their own personal and social search of the self and others. This experience is possible as a result of the foreign-born parents’ capability of reciprocal socialisation, sincere dialogue, and confrontation with the other (i.e. the native parents) in the diversity and richness of which each one is the bearer.